2021
DOI: 10.31557/apjcp.2021.22.8.2323
|View full text |Cite
|
Sign up to set email alerts
|

Association of PON1, LEP and LEPR Polymorphisms with Susceptibility to Breast Cancer: A Meta-Analysis

Abstract: Objective: Breast cancer is the most common cancer in American women, except for skin cancers. In this metaanalysis, the associations of polymorphisms within paraoxonase 1 (PON1), leptin (LEP) and leptin receptor (LEPR) genes with susceptibility to breast cancer were comprehensively evaluated. Methods: A universal search in PubMed, Scopus, CNKI, SID, Web of Knowledge and Google Scholar was performed to identify relevant studies up to 01 May, 2021. The strength of the associations was estimated by Odds ratios (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
2
2
Order By: Relevance
“…The current study contains more casecontrol studies with larger sample, making our results should be more reliable. It is worth mentioning that the results of a metaanalysis by Sayad et al 42 with only 14 case-control studies for Q223R published in 2021 were similar to ours. Our data also suggested that GG genotype of K109R in Asian population may also protect against BC, while AG genotype of K109R in Asian population may confer elevated susceptibility of BC.…”
Section: Discussionsupporting
confidence: 86%
“…The current study contains more casecontrol studies with larger sample, making our results should be more reliable. It is worth mentioning that the results of a metaanalysis by Sayad et al 42 with only 14 case-control studies for Q223R published in 2021 were similar to ours. Our data also suggested that GG genotype of K109R in Asian population may also protect against BC, while AG genotype of K109R in Asian population may confer elevated susceptibility of BC.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings supported this hypothesis by showing that LEP gene rs7799039 and ADIPOQ gene rs1501299 were two promising breast cancersusceptibility loci. By contrast, a recent meta-analysis by Sayad and coworkers did not support the association of LEP gene rs7799039 and LEPR gene rs1137100 with breast cancer (54). It is possibly because of the differing number of eligible studies involved between the meta-analysis by Sayad and coworkers (54) and the present meta-analysis.…”
Section: Discussioncontrasting
confidence: 65%
“…By contrast, a recent meta-analysis by Sayad and coworkers did not support the association of LEP gene rs7799039 and LEPR gene rs1137100 with breast cancer (54). It is possibly because of the differing number of eligible studies involved between the meta-analysis by Sayad and coworkers (54) and the present meta-analysis. As far as we know, we, for the first time, meta-analyzed the association between ADIPOQ gene and breast cancer.…”
Section: Discussioncontrasting
confidence: 65%
“…An estimated 287,850 new cases women were diagnosed with breast cancer in USA and 43,250 women will die from breast cancer in 2022 [ 4 , 5 ]. The occurrence of breast cancer is associated with many risk factors, including genetic and hereditary predisposition [ 6 , 7 ]. Breast cancers are highly heterogeneous [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%